Consensus clustering for urban land use analysis using cell phone network data. (16th October 2014) - Frias–Martinez, V.; Soto, V.; Sánchez, A.; Frias–Martinez, E.
Pervasive large–scale infrastructures have the ability to capture individual digital footprints and, as a result, provide a new vision on human dynamics. In this context, cell phones and cell phone networks, due to its ubiquity, can be considered one of the main sensors of human behaviour. The information collected by these networks can be used to understand the dynamics of urban environments with a detail not available up to now. One of the areas that can benefit from this information is urban planning. In this paper, we present a technique for the automatic identification of land uses from the information gathered by a cell phone network. Given the inherent diversity of human activities, we use consensus clustering to identify land uses, characterising only those geographical areas with well–defined behaviours. We present and validate our results using cell phone records and official land use data collected for Madrid.